Perancangan dan Validasi Artefak Kustomisasi Odoo untuk Integrasi Alur Pengepakan pada UMKM Ekspor - Armini, Ni Kadek Linda; Indradewi, Gusti Ayu Agung Diatri; Mahendra, Gede Surya (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
This study designs and validates a customized Odoo Inventory module artifact to address functional gaps in the operational processes of export-oriented SMEs, a context that remains underexplored in prior ERP customization research. A case study at CV Widhi Asih Bali Export identified that the standard Odoo Inventory module does not provide an integrated mechanism that bridges export order packing specifications, actual packing progress recording, and automated packing list issuance within a single system workflow. Using the DSR approach, the artifact was developed as an add-on module without modifying the Odoo core system, integrating three components: packing guide integration from Sales Order to Inventory module, integrated actual packing progress recording, and automated packing list generation from actual packing data. Functional testing across all operational scenarios confirmed that all three artifact components function as designed and produce consistent outputs. Validation through the informed argument approach involving the operations manager, IT staff, and packing staff confirmed that the artifact effectively bridges the system's functional gaps and precisely meets export operational requirements.